Implementasi Metode GADA (Grey Absolute Decision Analysis) untuk Penerimaan Pegawai - Manullang, Dosma Parningotan; Masrizal, Masrizal; Juledi, Angga Putra (LPPM UNIKA Santo Thomas Medan, 2023)
Poltekkes Kemenkes Medan is one of the many state campuses in the archipelago in the form of a Polytechnic, managed by the Ministry of Health and contained in the Ministry's Kopertis area. This campus has been established since January 1, 2001 with SK PT Number and SK PT Date, this Polytechnic is located on Jl. Jamin Ginting KM. 13.5 Ex. Lau Cih Medan – Tuntungan, district of Medan City, North Sumatra Province, Indonesia. the establishment of the Health Polytechnic is based on PP NO. 60 of 1999, then issued SK. Minister of Health No. 298/SK/Menkes/2001 which is a form of government policy in increasing the effectiveness of the use of available resources and sources of funds aimed at efficiency, a Health Polytechnic was formed. Recruitment is the process of finding and withdrawing workers who have the potential to fill vacancies, qualified workforce is very influential on the performance of the company's progress, the potential for making decisions about hiring prospective employees is still influenced by subjective factors and companies still often have difficulty in selecting employees, this research uses the method method. gray absolute decision analysis (GADA), because the gray absolute decision analysis (GADA) method is one of the multi-criteria settlement methods where there are many criteria that must be considered in recruitment.